Prevention of wasting and nutritional oedema: Evidence gaps identified during WHO guideline development - Ruel, Marie T.; Ashorn, Per; Berkley, James A.; Dewey, Kathryn G.; Golden, Kate; Huybregts, Lieven; McCaul, Michael; Naude, Celeste E.; Prinzo, Zita Weise; Daniel, Allison I. (BMJ, 2025)
Inclusion of prevention in the 2023 WHO guideline on wasting and nutritional oedema is a significant and timely addition, aligning with the global development goal of reducing current wasting prevalence from 6.6% to less than 3% by 2030. We identified three key evidence gaps in wasting prevention: Limited evidence on the effectiveness of wasting prevention interventions. Poor understanding of the challenges in implementing wasting prevention programmes. The absence of effective criteria for targeting wasting prevention interventions.